Measuring the Impact of TQM Pillars in Improving Banking Performance Using Quality Function Deployment; Afield Study of –CPA, BNA, BBA - Abdelatif, Oulad haimouda; Touaiti, Mustapha; CHenini, Abderrahim (Milev Journal of Research and Studies, 2021)
The aim of this study is to know the effect of applying TQM pillars on the development of determinants of banking performance; It was limited on the Algerian National Bank, the Algerian Popular Loan, Al Baraka Algerian Bank. In order to achieve the aims of the study, a descriptive method was adopted, and research was conducted on many sources of contemporary management though treated to the subject of the study.A questionnaire was developed for workers,(189 workers), in addition, the using the QFD model. The study concluded that the pillars of TQM have a positive effect on all determinants of banking performance in varying degrees. However, the quality of banking service has the highest score (741,512) and the "training and qualification of workers" pillar has the highest relative importance (13.42%), which means that the banks in the study give more priority to this pillar than the other pillars. On the other hand, the pillar of "motivating employees" was less important (10.63%), which means that the banks do not give much attention to this pillar.